Colonize with the look - Gil-Fernández, Rosalía (2019)
The purpose of this article is to visualize and analyze if the hegemonic way of looking at women established during colonial times en Latin America, in colonial times, still prevails nowadays, and if this look perpetuates a discourse of power structured and imposed, through specific techniques of subjection and appropriation, that have contributed in the construction of a marginal subjectivity. The proposal is that this look that produces inequality could possibly be reversed though the divulgation of the voices of those others, as a possible resistance to the colonial power, reflected in the Coloniality of Power that prevails in modern times. Key Words: Look, power, women, body, colony.